2020
DOI: 10.1175/ei-d-20-0002.1
|View full text |Cite
|
Sign up to set email alerts
|

Tigris Basin Landscapes: Sensitivity of Vegetation Index NDVI to Climate Variability Derived from Observational and Reanalysis Data

Abstract: The primary aim of this work is to study the response of the normalized difference vegetation index (NDVI) of landscapes in the Lower Tigris Basin to current global and regional climate variability presented, respectively, by the global circulation indices and monthly temperatures and precipitation extracted from five observational/reanalysis datasets. The second task is to find the dataset that best reflects the regional vegetation and climate conditions. Comparison of the Köppen-Trewartha bioclimatic landsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…After the diagnostic stage in which the function of the TFM rank (r, s, k) is determined and the chain of disturbance of the ARMA model, the parameters of the TFM described in equation (2) are evaluated as follows:…”
Section: Estimation and Validation Of Model Diagnostic Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…After the diagnostic stage in which the function of the TFM rank (r, s, k) is determined and the chain of disturbance of the ARMA model, the parameters of the TFM described in equation (2) are evaluated as follows:…”
Section: Estimation and Validation Of Model Diagnostic Accuracymentioning
confidence: 99%
“…Moreover, in many prediction situations, other events lead to a regular impact on the time series that we want to predict (dependent variables), so we need to use multivariate prediction models, and here we must build a prediction model that includes more than one-time series and shows the dynamic characteristics of the system. Such a model is called a transformation function model(TFM) [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of satellite NDVI data for a longer period allows vegetation changes assessment at global, regional and local scales (Measho et al, 2021). In the last three decades, it has been utilized for monitoring crop yield (Mkhabela et al, 2011), biodiversity (Madonsela et al, 2018), environmental degradation (Zhang et al, 2021), vegetation dynamics (Zarei et al, 2020), forest re susceptibility (Van Le et al, 2021), biological productivity (Alhumaima and Abdullaev, 2020), ecological environment (Sun et al, 2021), deserti cation (Li et al, 2021). Besides, it has been used to examine the in uence of climate variability on vegetation dynamics, droughts and environmental sustainability (Parmesan, C. 2006, Walther et al 2002, Bi et al 2013, Jiang et al 2017, Qi et al 2019Zhu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature forecasting can be studied for many seasonal cycles such as monthly, daily, hourly, or other periods. The temperature data is time-series data, and its observations are often by the nearest previous observation [2]. A previous study suggested forecasting temperature data in the literature using exponential smoothing models [3].…”
Section: Introductionmentioning
confidence: 99%